2016
DOI: 10.1186/s12966-016-0435-1
|View full text |Cite
|
Sign up to set email alerts
|

Parental involvement and association with adolescents’ fruit and vegetable intake at follow-up: Process evaluation results from the multi-component school-based Boost intervention

Abstract: BackgroundBased on the assumption of parental influence on adolescent behavior, multicomponent school-based dietary interventions often include a parental component. The effect of this intervention component is seldom reported and the evidence is inconsistent. We conducted a systematic process evaluation of the parental component and examined whether the leveal of parental involvement in a large multi-component intervention: the Boost study was associated with adolescents’ fruit and vegetable (FV) intake at fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
(53 reference statements)
0
9
0
Order By: Relevance
“…The comprehensiveness of our process evaluation is a strength but also a limitation, as it is not possible to perform an in-depth analysis of all the data collected regarding all features and all informant groups. Another option would have been to cut the process evaluation results into slices for each component and informant, such as presenting the evaluation of the curriculum component via teacher interviews in one paper [35] and the parental component via parent surveys in another paper [36]. Our choice provides an overview of the complexity, but the presentation of each aspect is brief.…”
Section: Discussionmentioning
confidence: 99%
“…The comprehensiveness of our process evaluation is a strength but also a limitation, as it is not possible to perform an in-depth analysis of all the data collected regarding all features and all informant groups. Another option would have been to cut the process evaluation results into slices for each component and informant, such as presenting the evaluation of the curriculum component via teacher interviews in one paper [35] and the parental component via parent surveys in another paper [36]. Our choice provides an overview of the complexity, but the presentation of each aspect is brief.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining studies (n 37) were not included in the meta-analysis because of various factors: necessary information could not be obtained (i.e. no control group (43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56) ; control is another intervention (57,58) ; unstandardised effect size (49,59,60) ; not an actual consumption (15,(61)(62)(63)(64)(65)(66)(67)(68) and no sample size) (69) ; tracking studies (i.e. dietary intervention initiated in childhood and tracked/followed up into adulthood) (34,70) and studies were rated as weak (71)(72)(73)(74)(75)(76)(77) .…”
Section: Literature Searchmentioning
confidence: 99%
“…The majority of the studies distributed solely FV as a snack (i.e. stand-alone intervention), whereas some studies in addition to providing FV, integrated other supplementary/reinforcement components such as nutrition education (34,38,60,67,78) , parental involvement (33,44,49,56,68,79) , peer modelling and rewards (46,50,57,58) . Most of the study interventions were guided by the constructs of social cognitive theory (SCT) (n 13) (80) , Intervention Mapping Protocol (IMP) (n 7) (81) and utilisation-focused Participatory Approach (82) .…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Baltimore Healthy Eating Zones (BHEZ), a childhood obesity prevention trial conducted at multiple levels in the low-income urban area of Baltimore City, used different components of the intervention to create an exposure score to inform a secondary evaluation analysis [ 15 ]. The Boost program, a Danish multi-component school-based trial, used measures of exposure as the extent of parental involvement in the intervention, and found that students with a high exposure level consumed more fruits and vegetables daily than those with a low exposure score [ 16 ].…”
Section: Introductionmentioning
confidence: 99%